Analysis of the surface texture and parametric optimization of wire-EDM process - Wang, Zhi Qiang. (2009)
This thesis is concerned with the wire electrical discharge machining (Wire-EDM) process and the corresponding surface texture. Wire-EDM technology has been widely used in production, aerospace/aircraft, medical and virtually all areas of conductive material machining. Its complexity and stochastic nature have stimulated numerous attempts of describing it accurately.